Huangqi-Danshen Decoction Ameliorates Adenine-Induced Chronic Kidney Disease by Modulating Mitochondrial Dynamics. (1st January 2019) - Liu, Xinhui; Huang, Shiying; Wang, Fochang; Zheng, Lin; Lu, Jiandong; Chen, Jianping; Li, Shunmin
Abstract : Chronic kidney disease (CKD) is a leading public health problem with high morbidity and mortality. However, the therapies remain limited. Traditional Chinese medicine (TCM) has been used for treating kidney disease for thousands of years and is an effective alternative treatment for CKD patients in China and other Asian countries. In the present study, we aimed to investigate the effect and mechanism of Huangqi-Danshen decoction (HDD), a TCM herbal decoction, on treating CKD. CKD rat model was induced by adding 0.75% adenine to the diet for 4 weeks. HDD extract was administrated orally to CKD rats at the dose of 4.7 g/kg/d for consecutive 4 weeks in adenine-induced CKD rats. Kidney function was evaluated by the levels of serum creatinine (Scr) and blood urea nitrogen (BUN). The pathological changes of kidney tissues were observed by periodic acid-Schiff (PAS) and Masson's trichrome staining. The proteins expression of renal fibrosis and mitochondrial dynamics were determined and quantified by Western blot analysis. CKD rats showed obvious decline in renal function as evidenced by increased levels of Scr and BUN, which were blunted by HDD treatment. HDD could also improve tubular atrophy and interstitial fibrosis of CKD rats. Moreover, HDD downregulated fibronectin, type IV collagen, and α -smooth muscle actin expression in CKD rats. Furthermore, mitochondrial dynamics was disturbed in CKD rats, which manifested as increased mitochondrial fission and decreased mitochondrial fusion. HDD treatment restored mitochondrial dynamics in CKD rats by repressing dynamin-related protein 1 and Mid 49/51 expression, promoting mitofusin 2 expression, and suppressing optic atrophy 1 proteolysis. In conclusion, HDD could significantly retard CKD progression through modulating mitochondrial dynamics.